2012
DOI: 10.1088/0004-637x/749/2/169
|View full text |Cite
|
Sign up to set email alerts
|

The Mid-Infrared Environments of High-Redshift Radio Galaxies

Abstract: Taking advantage of the impressive sensitivity of Spitzer to detect massive galaxies at high redshift, we study the mid-infrared environments of powerful, high-redshift radio galaxies at 1.2 < z < 3. Galaxy cluster member candidates were isolated using a single Spitzer/IRAC mid-infrared color criterion, [3.6] − [4.5] > −0.1 (AB), in the fields of 48 radio galaxies at 1.2 < z < 3. Using a counts-in-cell analysis, we identify a field as overdense when 15 or more red IRAC sources are found within 1 ′ (i.e., 0.5 M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
143
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(152 citation statements)
references
References 59 publications
9
143
0
Order By: Relevance
“…A large number of imaging and spectroscopic studies have demonstrated conclusively that many massive radio galaxies at z ≥ 2 are surrounded by galaxy overdensities at the same redshift, as well as significant reservoirs of molecular, atomic, and ionized gas, including diffuse intra-halo gas (Le Fèvre et al 1996;Venemans et al 2007;Hayashi et al 2012;Galametz et al 2012;van Ojik et al 1997;Villar-Martín et al 2003;De Breuck et al 2003;Nesvadba et al 2009;Wylezalek et al 2013;Collet et al 2015). With the small field of view of only 8 × 8 , SINFONI can only constrain the very nearby environment of HzRGs out to a few tens of kpc (8 correspond to 64 kpc at z ∼ 2); however, this small-scale environment is particularly interesting, e.g., to study how accretion and merging may affect the evolutionary state of the radio galaxy.…”
Section: Additional Line Emitters and Dynamical Mass Estimates Of Ourmentioning
confidence: 99%
“…A large number of imaging and spectroscopic studies have demonstrated conclusively that many massive radio galaxies at z ≥ 2 are surrounded by galaxy overdensities at the same redshift, as well as significant reservoirs of molecular, atomic, and ionized gas, including diffuse intra-halo gas (Le Fèvre et al 1996;Venemans et al 2007;Hayashi et al 2012;Galametz et al 2012;van Ojik et al 1997;Villar-Martín et al 2003;De Breuck et al 2003;Nesvadba et al 2009;Wylezalek et al 2013;Collet et al 2015). With the small field of view of only 8 × 8 , SINFONI can only constrain the very nearby environment of HzRGs out to a few tens of kpc (8 correspond to 64 kpc at z ∼ 2); however, this small-scale environment is particularly interesting, e.g., to study how accretion and merging may affect the evolutionary state of the radio galaxy.…”
Section: Additional Line Emitters and Dynamical Mass Estimates Of Ourmentioning
confidence: 99%
“…Antonucci 1993), the hot dust near central active galactic nuclei (AGN) is completely obscured by material along the line of sight in type 2 AGN, and becomes gradually less obscured when transitioning to type 1 AGN (e.g., Leipski et al 2010;Drouart et al 2012;Rawlings et al 2013). Spitzer observations also revealed that high-redshift radio galaxies are preferentially found in denser environments, consistent with galaxy clusters in formation (e.g., Mayo et al 2012;Galametz et al 2012;Wylezalek et al 2013a,b).…”
Section: Introductionmentioning
confidence: 95%
“…The questions of when and how present-day galaxy clusters formed at high redshift have driven extensive searches for protoclusters of galaxies in the distant Universe in the past two decades (e.g., Le Fevre et al 1996;Steidel et al 1998;Pentericci et al 2000;Kurk et al 2000Kurk et al , 2004aBest et al 2003;Matsuda et al 2005;Daddi et al 2009a;Galametz et al 2010;Galametz et al 2012;Hatch et al 2011a,b;Mayo et al 2012;Walter et al 2012;Wylezalek et al 2013). Powerful high-redshift radio galaxies (HzRGs; see the review by Miley & De Breuck 2008) LABOCA and VLA images (FITS files) are only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/570/A55 are considered to be the most promising signposts of the most massive clusters in formation.…”
Section: Introductionmentioning
confidence: 99%